2013
DOI: 10.1272/jnms.80.362
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coexisting Irritable Bowel Syndrome and Non-erosive Reflux Disease on Postprandial Abdominal Fullness and Sleep Disorders in Functional Dyspepsia

Abstract: Symptom scores, such as those for postprandial abdominal fullness, heartburn, and the feeling of hunger, in patients with FD-overlap syndromes are significantly greater than those in patients with FD alone. Further studies are necessary to clarify whether various symptoms are related to sleep disorders in patients with FD-NERD-IBS overlap syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Ford et al have also reported that the incidence of IBS is 8 times higher in subjects with FD and suggests that IBS and FD share the process of the progression of their diseases (14). In our data, the severity of symptom, such as heartburn and hunger in the overlapped syndrome were significantly higher compared to that in FD patients (15).…”
supporting
confidence: 56%
“…Ford et al have also reported that the incidence of IBS is 8 times higher in subjects with FD and suggests that IBS and FD share the process of the progression of their diseases (14). In our data, the severity of symptom, such as heartburn and hunger in the overlapped syndrome were significantly higher compared to that in FD patients (15).…”
supporting
confidence: 56%
“…In Japan, the rate of FD and IBS overlap varied significantly from 10% to 56%. 52,53 In Korea, the overlap rate was found to be 27%. 3 The high rate of FD and IBS overlap in East and Southeast Asia is in general similar to rates in Western countries.…”
Section: Functional Dyspepsia In East and Southeast Asiamentioning
confidence: 99%
“…An important overlap is present between FD and IBS with both occurring in 30% and 60% of patients, respectively 10 . Overlap may be more common in patients with severe symptoms than in patients with mild symptoms and in PDS than in EPS, especially in patients with postprandial fullness 10 , 21 , 22 . Moreover, longitudinal studies demonstrate that the risk of a patient with FD developing IBS is increased by up to eightfold compared with the general population 23 .…”
Section: Diagnosismentioning
confidence: 99%